Identifying recruitment strategies to improve the reach of evidence-based health promotion, disease prevention, and disease self-management interventions: a scoping review - Estabrooks, Paul A.; Bolyard, Mickey L.; Casucci, Tallie; Christensen, Josh T.; Gibson, Bryan; Golden, Caitlin A.; Hill, Jennie L.; Horvath, Linnea; Lee, Shinduk; Maxfield, Ellen M.; McFarland, Mary M.; Merle, James L.; et al. (Frontiers in Public Health, 2025)
IntroductionImproving the reach of existing lifestyle interventions focused on health promotion, disease prevention, and self-management delivered in community or clinical settings has the potential to increase the public health impact of these interventions. However, little is known about the overall success of recruitment strategies or the specification of strategy components including the details of how, through which channel, and by whom the recruitment strategies are enacted.MethodsWe conducted a scoping review with guidance from the JBI Manual for Evidence Synthesis. For transparency and reproducibility, we adhered to the PRISMA-S and PRISMA-ScR guidelines for reporting literature searches and scoping reviews. Our eligibility criteria included studies that reported recruitment strategies to improve reach (enrollment number, participation rate, and representativeness of participants) of health promotion, disease prevention, and self-management lifestyle interventions for children or adults worldwide. Recruitment strategies for non-lifestyle interventions, such as pharmaceutical trials, were excluded. Databases included Medline (Ovid), Embase (embase.com), CINAHL Complete (Ebscohost), APA PsycINFO (Ebscohost), and Dissertation and Theses Global (ProQuest). Database search results were retrieved on March 2–3, 2023.ResultsFrom a total of 9,712 references, 98 studies were included. Eight studies compared recruitment strategies using a randomized controlled trial and 90 studies were evaluations/quasi-experiments that reported on reach. There was a wide variety of recruitment strategies used, with 32% of the studies utilizing more than one recruitment strategy. The average reach, operationalized as participation rate, of the primary strategy (n = 15 defined strategies) being tested ranged from 3 to 41%. Further, participation rates ranged across studies that focused on children (43%), adults (25%), and older adults (16%). Most included studies did not report (1) strategy timing and dose, (2) theoretical basis, or (3) potential mechanisms of improved reach. Finally, differences in how the denominator was operationalized reduced confidence in comparing across strategies.DiscussionMore clarity is needed when reporting on specific recruitment strategies used to improve the reach of lifestyle interventions. Suggestions include guidance on how to consistently define a denominator of eligible participants exposed to recruitment strategies. Furthermore, the use of theoretical approaches and testing of potential mechanisms of effect are needed in future studies to advance the science of improving lifestyle intervention reach.Systematic review registrationThe unique identifier for our scoping review is 3g68b it can be found at this url: https://doi.org/10.17605/OSF.IO/3G68B.